Resilience and Place Identity in the Context of the Global Climate Emergency: A Comparative Study in Brazil and Portugal - Camargo, Alexandro Francisco; Basílio, Romário Sampaio (Sociedade & Natureza, 2025)
In this comprehensive study, Portuguese university students were compared with Brazilian counterparts on the parameters of place identity and resilience traits. To this end, following data collection via a questionnaire, psychometrics was combined with statistical analysis methods, with the primary goal of understanding how place identity and resilience contribute to fostering climate resilience. The results reveal a generally accurate perception among participants regarding the consequences of climate change in their respective regions, with a more pronounced awareness observed in areas predicted to experience greater climate changes. Notably, in Portugal, a significant correlation emerged between a heightened risk of floods and stronger local identity, whereas among Brazilian participants, a similar correlation was observed with dry conditions. This presentation focuses on the analysis of Local/Social Identity and Resilience (Takviriyanun scale). The results also highlight a predominantly positive connection between participants and their local communities. It is noteworthy that individuals with a stronger sense of local identity demonstrate greater resilience in four out of the five factors analyzed (Support, Determination, Optimism, and Other Supports). It is concluded, therefore, that a strengthened local identity is associated with an increased capacity to cope with climate change. In this way, the possibility arises to analyze the relationship between place identity and resilience as an essential psychogeographic concept for territorial management, as it emerges as a strategic tool to promote and enhance adaptation processes.